Trust inside a political organization : a case study of the Finnish Centre Party parliamentary group - Salmisalo, Katariina (2011)
This thesis examined trust inside a political organization as well the relation between trust and creativity. The thesis is a case study of the Finnish Centre Party Parliamentary Group. The research sought answers for the questions how professional politicians (members of the parliament) experience trust inside the party they are members of, and whether trust in a political organization brings added value for the organization. The focus was on the formation process of trust and factors grounded in this process. The role of trust for creativity was also of interest.